1991
DOI: 10.1148/radiology.180.2.2068303
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose high-resolution CT of lung parenchyma.

Abstract: To evaluate the efficacy of low-dose high-resolution computed tomography (HRCT) in the assessment of lung parenchyma, three observers reviewed the scans of 31 patients. The 1.5-mm-collimation, 2-second, 120-kVp scans were obtained at 20 and 200 mA at selected identical levels in the chest. The observers evaluated the visualization of normal pulmonary anatomy, various parenchymal abnormalities and their distribution, and artifacts. The low-dose and conventional scans were equivalent in the evaluation of vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
76
0
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 0 publications
0
76
0
6
Order By: Relevance
“…Whilst REMY-JARDIN et al [5] found upper zone-predominant micronodules in 26 (27%) out of 98 asymptomatic smokers, we found signs of RB in 109 (15.7%) out of 692 smokers despite the fact that individuals recruited by MILD were heavier smokers. Such a discrepancy may have several explanations: in particular, the use of a low-dose CT protocol in our lung cancer screening trial may have lowered the detection rate of hazy nodules and ground-glass opacity [21]. Furthermore, in contrast with another study of REMY-JARDIN et al [22], which showed changes of centrilobular nodules over a mean period of 5.5 yrs in 11 (64.7%) out of 17 smokers, only five (12%) out of 42 cases with centrilobular nodules displayed changes after 3 yrs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst REMY-JARDIN et al [5] found upper zone-predominant micronodules in 26 (27%) out of 98 asymptomatic smokers, we found signs of RB in 109 (15.7%) out of 692 smokers despite the fact that individuals recruited by MILD were heavier smokers. Such a discrepancy may have several explanations: in particular, the use of a low-dose CT protocol in our lung cancer screening trial may have lowered the detection rate of hazy nodules and ground-glass opacity [21]. Furthermore, in contrast with another study of REMY-JARDIN et al [22], which showed changes of centrilobular nodules over a mean period of 5.5 yrs in 11 (64.7%) out of 17 smokers, only five (12%) out of 42 cases with centrilobular nodules displayed changes after 3 yrs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although reduction of the milliamperage increases the image noise, NAIDICH et al [29] found that visualization of parenchymal structure was not affected by decreasing the milliamperage. ZWIREWICH et al [30] showed that the low-dose and the standard-dose HRCT scans were equivalent in the evaluation of anatomical information as well as interstitial and air-space abnormalities. A recent study reported that low-dose spiral CT was equivalent to the standard-dose spiral CT at visualizing lung abnormalities [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT should be performed within objective parameters that make lesion depiction reliable and reproducible. Generally, a tube current of 200 -400 mA is acceptable (13,14). Low tube current may produce excessive noise that simulates ground-glass opacity or may lead to the failure to depict ground-glass opacity (14).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Generally, a tube current of 200 -400 mA is acceptable (13,14). Low tube current may produce excessive noise that simulates ground-glass opacity or may lead to the failure to depict ground-glass opacity (14). In this context, low-dose CT probably would not be appropriate for characterizing nodular ground-glass opacity (Fig 1).…”
Section: Technical Considerationsmentioning
confidence: 99%